The parental bonding instrument: a psychometric measure to assess parenting practices in the homes in Bangladesh - Karim, A.K.M. Rezaul; Begum, Taslima (© 2017 Elsevier., 2019)
This article was published in the Asian Journal of Psychiatry [© 2017 Elsevier Ltd.] and the definite version is available at : https://doi.org/10.1016/j.ajp.2016.11.004. The Journal's website is at: https://www.sciencedirect.com/science/article/pii/S1876201816302921#kwd0005.